Nilai Filosofis Tata Ruang Bangunan Tradisional Bali dalam Teks Asta Kosala Kosali - Ni Luh Komang Indah Sari; I Made Wirahadi Kusuma (Sphatika: Jurnal Teologi, 2020)
The concept of Balinese Architecture in the arrangement of the spatial value of traditional Balinese buildings which includes in the Asta Kosala Kosali text, provides the spatial design and layout of the building so that it has a philosophical value at the position of certain buildings. Structuring the building is supported by the concept of Tri Angga, Tri Mandala and lontar Asta Bhumi which can be in harmony between one building with another. The structure of this building can be seen from the shape of Padma Bhuwana which regulates the direction and symbol of the building. This can be influenced by values ​​/ spirituality, conditions / potentials owned, and economic commodities owned in the area that will be built.